Esquemas de argumentação para discussão de riscos em projetos de software - Pozzebon, Ruan Carlo Bonilha (2014)
Risk management is a key component of project management, which aims to identify, analyze and treat possible events that can compromise project success. In this context, the proposition and the improvement of technical processes that support risk management is a constant need, in particular seeking to standardize and formalize collaborative discussions of risks in software projects, for example. In this context, the use of alternative techniques of argumentation in the area of Artificial Intelligence applied to the area of risk management is discussed in this paper. This work presents schemes for argument proposition and discussion of risks, together with techniques of dialogue games, which aim to mediate collaborative discussions of risks in software projects. These schemes are designed to help novice users to propose risks, which can be described by well-trained and structured arguments. Furthermore, the paper discusses how to promote continuity and depth discussion of the risks with a set of critical issues, which make up the structure of the proposed schemes. The paper also presents a process for creation / standardization of argumentation schemes meant for this application domain. In particular, this construction process presents steps required to create arguments schemes in the area of risk management. From the use of this process, the development of regimens may be better understood, allowing the extension of this schema library and the consequent use of these schemes discussions risks. Based on the proposed schemes, this work presents a web system - Risk Discussion System (RD System v2.0) - built to provide a collaborative environment for discussions of risk, where different forms implemented and tested in our project can use schemes. In order to validate the approach proposed in this paper, two experiments were conducted. The results of these experiments show positive evidence for the acceptance and applicability of the approach in collaborative discussions of risks, as well as an increase in quality of the information typically managed through other risk management strategies.